Alveolar macrophage dysfunction in malignant lung tumours. - Lemarie, E (1984)
Alveolar macrophage chemotaxis was measured in 129 individuals--13 normal volunteers, 15 tumour free patients with recent bronchopulmonary infections, 10 patients with chronic bronchitis, 29 patients with endothoracic sarcoidosis, 48 patients with primary bronchial carcinoma and 14 patients with pulmonary metastases from various origins. Chemotaxis was tested in the presence of either zymosan activated autologous serum, N-formyl-methionine-leucyl-phenylalanine (F-Met-Leu-Phe), or zymosan activated human AB serum. Alveolar macrophage chemotaxis was significantly less in patients with bronchial carcinoma than in healthy volunteers (p less than 0.01). Chemotaxis was significantly more depressed in samples obtained from the neighbourhood of the tumour than in samples from the opposite lung. Defective chemotaxis was also found in patients with sarcoidosis. In contrast, the presence of lung metastases did not affect chemotaxis. A recent bronchopulmonary infection was associated with significantly increased (p less than 0.02) chemotaxis in tumour free patients but not in patients with a primary lung tumour. The findings suggest that an intrinsic functional defect of alveolar macrophages might favour the development of bronchogenic carcinoma.